Synthesis and evaluation of 68Ga labeled palmitic acid for cardiac metabolic imaging. (October 2018) - Jain, Akanksha; Mathur, Anupam; Pandey, Usha; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract: This work evaluates the potential of a 68 Ga labeled long chain 16C fatty acid for cardiac metabolic imaging. For radiolabeling with 68 Ga, hexadecanedioic acid was coupled with the chelator p -NH2 -Bn-NOTA. Under the optimized conditions, NOTA-hexadecanoic acid could be radiolabeled with 68 Ga in ≥95% yields. In biodistribution studies carried out in Swiss mice, 68 Ga-NOTA-hexadecanoic acid showed low myocardial uptake at 2 min p.i. (3.7 ± 1.3%ID/g). While 68 Ga-NOTA-hexadecanoic acid cleared rapidly from non-target organs such as blood, lungs, intestine and kidney, wash out from liver was slow. Radio-HPLC analyses of myocardial extracts of rats injected with 68 Ga-NOTA-hexadecanoic acid confirmed its metabolic transformation in the myocardium. Highlights: NOTA-hexadecanoic acid synthesized and characterized by 1 H NMR and ESI-MS. NOTA-hexadecanoic acid radiolabeled with 68 Ga in >95% yields. Formation of 68 Ga-conjugate confirmed by characterization of its nat Ga surrogate. Myocardial uptake of 68 Ga-conjugate was 3.7 ± 1.34%ID/g at 2 min p.i. Heart metabolite analysis showed metabolic transformation of fatty acid conjugate.